Republic of Croatia : Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines the Croatia's Request for a Stand-By Arrangement (SBA). Despite a disappointing merchandise trade performance, strong exports of services and private transfers have helped restrain the current account deficit. The authorities' program for 2003 constitutes a major step toward long-term fiscal sustainability and higher economic growth. The authorities recognize that more needs to be done in the future to boost the population's standard of living and put Croatia on a firm path of real convergence with the European Union. The IMF staff supports the authorities' request for a SBA.